2017
DOI: 10.3892/ol.2017.6435
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the RAS/RAF/MEK/ERK signaling pathway in 260 Han Chinese patients with cervical carcinoma

Abstract: Abstract. Prevalent mutations in the mitogen-activated protein kinase 1 (MAPK1)/extracellular signal-regulated kinase 2 (ERK2) pathway have been identified in cervical squamous cell carcinoma in a large-scale genome sequencing effort. Furthermore, mutations in the rat sarcoma viral oncogene homolog (RAS)/Raf/Mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) signaling pathway have also been revealed to have important roles in the pathogenesis of human cancer. However, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…β-catenin functions as a powerful trans-activator of T-cell factor/lymphoid enhancer factor transcription factors, which regulate important downstream target genes that promote cell proliferation, differentiation and tissue development. The MEK signaling pathway comprises several key signaling components and phosphorylation events that have important roles in tumorigenesis ( 26 , 27 ). These activated kinases regulate cell growth, differentiation, proliferation and migration ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin functions as a powerful trans-activator of T-cell factor/lymphoid enhancer factor transcription factors, which regulate important downstream target genes that promote cell proliferation, differentiation and tissue development. The MEK signaling pathway comprises several key signaling components and phosphorylation events that have important roles in tumorigenesis ( 26 , 27 ). These activated kinases regulate cell growth, differentiation, proliferation and migration ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three studies (31%) with 2,983 participants reported this mutation [ 6 , 13 , 15 , 30 , 31 , 35 , 37 , 42 , 43 , 62 , 63 , 70 , 72 , 73 , 75 77 , 79 , 84 , 86 , 87 , 89 , 91 ]. The combined positivity rate was 14% (95%CI: 8%–21%; I 2 = 95%, Figure 7, Appendix D ); however, considering the substantial, heterogeneity, the positivity rate ranged between 0% and 82%.…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant activation of this pathway is common in several cancers, including CC, which often results from the presence of mutations and ampli cations of KRAS. For instance, Zou Y. and collaborators, reported that the frequency of the KRAS mutation ranged from 8.0-17.5% in cervical ADC [35], to absent or rare in SCC, which suggested that KRAS mutations are frequent and might be a driving factor for the development of cervical ADC but not SCC [36], [37]. Although, in our study we observed that Ras pathway has a higher level of activation in SCC than ADC, which may be due to mutations or alterations in other elements of the pathway [35].…”
Section: Discussionmentioning
confidence: 99%